Peringkat Obligasi Korporasi: Faktor Internal Perusahaan - Abdul Latif (Faculty of Economics, Universitas Internasional Batam, 2022)
Purpose - Bonds are one of the sources of corporate funding. This funding is very efficient and more efficient than funding through banks, significantly since the issuance of corporate bonds fluctuates yearly, which means there is active issuance of corporations. Therefore, there is a lot of interest from investors in choosing corporate bonds. As one of the long-term investment instruments. From this background, the researcher aims to analyze how much and how much influence (1) company size to bond rating, (2) profitability against bond ratings, (3) leverage on bond ratings. Research Method - The method in this study belongs to the type of causality with a quantitative analytical application, the population in this study is non-bank corporate bonds and financial institutions that are still traded in 2021, with a sample of 230 corporate bonds from 37 issuing companies. Used is ordinal logistic regression, with SPSS 25 analysis tool. Findings - The results of this study indicate that company size harms corporate bond ratings, profitability projected by return on assets, and leverage launched by debt-equity ratio does not affect corporate bond ratings. Implication - From the results of this study, it is hoped that issuers can prepare and fix the factors that can improve bond ratings so that the bonds issued are low in default risk and for investors to consider by analyzing the factors that have been studied in this study in investing and avoiding the risk of default bonds and can determine healthy bonds in the long term.